Characterisation of Chinook salmon (Oncorhynchus tshawytscha) blood and validation of flow cytometry cell count and viability assay kit. Issue 88 (May 2019) - Lulijwa, Ronald; Alfaro, Andrea C.; Merien, Fabrice; Burdass, Mark; Young, Tim; Meyer, Jill; Nguyen, Thao V.; Trembath, Caroline
Abstract: New Zealand Chinook salmon ( Oncorhynchus tshawytscha ) industry has great potential for growth and expansion. While production is relatively free of health problems, there is limited literature on haematology, and immunological tools to safeguard against possible future health threats. The current study aim was to characterise New Zealand farmed O. tshawytscha peripheral blood cellular composition, develop a micro-volume method to isolate peripheral blood mononuclear cells (PBMCs) and validate a microcapillary flow cytometry assay kit for PBMC cell count and viability assessment. We used light microscopy to characterise peripheral blood and PBMC cellular composition in combination with a flow cytometer Sysmex XT 2000i Haematology Analyser. ImageJ version 1.52 was used for cell size characterisation of freshly stained blood. The stability of PBMCs stained with the Muse ® Cell Count and Viability Assay Kit and the Trypan blue assay stains were studied at 4 °C and 21 °C for 60 min; while the Muse ® Cell Count and Viability Assay Kit was validated against the Trypan blue assay haemocytometer chamber to assess PBMC count and viability. Findings showed that O. tshawytscha smolt yearlings had total blood cell counts in the range of 1.9–2.7 × 10 6 μL −1 . Differential cell counts revealed five cell types, comprising 97.18% erythrocytes, 2.03% lymphocytes, 0.67% thrombocytes, 0.09% monocytes, and unquantifiable neutrophils. Using micro-volumes of blood and Lymphoprep™, we successfully isolated fish PBMCs. Significantly, stained PBMCs remained stable for up to 45 min at 4 °C and 21 °C; while validation of the Muse ® protocol showed that this microfluidic instrument delivered more accurate and precise viability results than the haemocytometer. The Muse ® protocol is rapid, easy to use, has quick calibration steps, and is suitable for field use to facilitate onsite sample processing. These findings pave the way for future assessments of fish health and in vitro immunological studies in O. tshawytscha . Graphical abstract: Image 1 Highlights: Salmon smolts peripheral blood total cell count was estimated at 2.3 × 10 6 μL −1 . Differential cell counts revealed five cell types dominated by 97.18% erythrocytes. Fish PBMCs successfully isolated from a micro blood volume (<300 μL). Isolated PBMCs were majorly composed of lymphocytes and monocytes. Muse ® Cell Analyser delivered accurate and precise results as the haemocytometer.